The answer to 6y times y is 6y^2. This is because when you multiply two terms with the same base (y in this case), you add the exponents. In this case, the exponent on y is 1 for both terms, so 1 + 1 = 2, giving us y^2. The coefficient 6 remains unchanged in the final answer.
In mathematics, when you multiply a number by another number, you are essentially adding the number to itself the specified number of times. Therefore, when you multiply Y by 6, you are adding Y to itself 6 times. This can be represented as Y + Y + Y + Y + Y + Y, which simplifies to 6Y. So, Y times 6 is equal to 6Y.
2
2
6 - y + 5y - 6y = 6 - 2y
If 6y-8 = 28 then y = 6
In mathematics, when you multiply a number by another number, you are essentially adding the number to itself the specified number of times. Therefore, when you multiply Y by 6, you are adding Y to itself 6 times. This can be represented as Y + Y + Y + Y + Y + Y, which simplifies to 6Y. So, Y times 6 is equal to 6Y.
y < 18*6y < 18*6y < 18*6y < 18*6
in respect to y 2y*3-y collecting the three times the coefficient of y which is 2 6y-y 6y-y=5y the derivative of 5y in respect to y is 5.
6y + 1 = 19 Therefore, 6y = 18 y = 18/6 y = 3
6y-1+8=32 y=4 1/6 Here's the steps- 6y-1+8=32 6y+7=32 6y=25 y=4 1/6
6y + 11 = 23 6y = 23 - 11 6y = 12 y = 12/6 y = 2.
6 - y + 5y - 6y = 0 6 = y -5y + 6y 6 = -4y + 6y 6 = 2y 6/2 = y 3 = y
-6y + 5 = -67y=12-6y = -72-y = -12y = 12
6y+1=19 6y=20 y=20/6=10/3~=3.333
8 + 6y
2
2